Lawrence of Arabia (Columbia Pictures, 1962)
A historical drama re-creating the legend of a gifted soldier and true independent spirit, T. E. Lawrence, and his accomplishments in the World War I desert campaign in which he led the Arabs against the Turks in the 1920s.